Shot peening optimisation by means of 'DOE': Numerical simulation and choice of treatment parameters. (4th August 2014) - Baragetti, S.
Shot peening is widely used to improve the fatigue properties of cyclically loaded mechanical components. The benefits of the treatment, which are mainly due to the compressive residual stress field induced in the surface layers of material, depend on the correct choice of the peening parameters. However, many times the choice of the treatment parameters is made by following empirical considerations, that do not make it possible, for the particular mechanical application, to set the most important factors at their best levels. So, an appropriate procedure, suitable for the different applications, would be necessary to optimise the treatment parameters and to address the choice of their best levels. 'Design of Experiment' (DOE) was applied to the results obtained from the numerical simulation of shot peening (impact of one or more spheres on an infinite smooth steel target), and permitted a choice to be made of the best levels of the treatment parameters in a cheap and fast way.